2010
DOI: 10.1007/s00415-010-5514-7
|View full text |Cite
|
Sign up to set email alerts
|

A comparative assessment of cerebral white matter by magnetization transfer imaging in early- and adult-onset multiple sclerosis patients matched for disease duration

Abstract: A more favorable clinical course in early-onset (EO) multiple sclerosis (MS) than adult-onset (AO) disease is reported. Our aim was to assess white matter with/without lesions by magnetization transfer (MT) imaging in EO and AO MS patients matched for duration of the disease. Relapsing-remitting MS patients with disease onset at age < or =18 years and >18 years (n = 11 for each) were matched according to sex, age, disease duration, and 22 sex-and age-matched healthy subjects were studied with MT imaging. MT ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…69 Abnormal MTR was also reported in normal-appearing brain tissue in a study of 11 adolescents and 11 adults with multiple sclerosis compared with 22 healthy controls. 70 Further studies of large cohorts followed for long periods of time are needed to fully appreciate MTR analyses in paediatric multiple sclerosis cohorts.…”
Section: Mri In Paediatric Multiple Sclerosismentioning
confidence: 99%
“…69 Abnormal MTR was also reported in normal-appearing brain tissue in a study of 11 adolescents and 11 adults with multiple sclerosis compared with 22 healthy controls. 70 Further studies of large cohorts followed for long periods of time are needed to fully appreciate MTR analyses in paediatric multiple sclerosis cohorts.…”
Section: Mri In Paediatric Multiple Sclerosismentioning
confidence: 99%
“…Finally, in an MTR study comparing 22 age-matched controls with 22 RRMS subjects with disease onset either before age 18 (mean age at scan 21.3, range 15–29) or after age 18 (mean age at scan 37.6 years, range 25–48), Oguz et al (2010) found reduced MTR in the NAWM when compared to controls, but no age-related effect between the two MS groups.…”
Section: Discussionmentioning
confidence: 92%